2021
DOI: 10.1007/s00404-021-05975-2
|View full text |Cite
|
Sign up to set email alerts
|

Does hysteroscopic resection of uterine septum improve reproductive outcomes: a systematic review and meta-analysis

Abstract: Purpose Uterine septum in women with subfertility or previous poor reproductive outcomes presents a clinical dilemma. Hysteroscopic septum resection has been previously associated with adverse reproductive outcomes but the evidence remains inconclusive. We aimed to thoroughly and systematically appraise relevant evidence on the impact of hysteroscopically resecting the uterine septum on this cohort of women. Methods AMED, BNI, CINAHL, EMBASE, EMCARE, Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A meta-analysis on this topic concluded that septum resection was associated with a lower rate of miscarriage compared with untreated women and no significant effect was seen on live birth, clinical pregnancy rate or preterm delivery [ 75 ]. Although interesting, this meta-analysis is incomplete considering the poor number of papers included (only seven) and the fact that all patients were evaluated together without distinction between infertile patients and patients with recurrent miscarriage.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…A meta-analysis on this topic concluded that septum resection was associated with a lower rate of miscarriage compared with untreated women and no significant effect was seen on live birth, clinical pregnancy rate or preterm delivery [ 75 ]. Although interesting, this meta-analysis is incomplete considering the poor number of papers included (only seven) and the fact that all patients were evaluated together without distinction between infertile patients and patients with recurrent miscarriage.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…Similarly, a recent meta-analysis involving 7 studies demonstrated a lower miscarriage rate in the hysteroscopic septum resection group compared to the expectant management group, but clinical pregnancy, live, and preterm rates were similar. [ 28 ] In addition, in patients with RPL, the rate of term pregnancy after surgery was found to be quite successful with 66%.…”
Section: Discussionmentioning
confidence: 99%
“…21 Retrospective studies reported reduced abortion rates and increased live birth rates in patients who underwent hysteroscopic metroplasty compared to untreated patients. 22 Recentely, a meta-analysis involving seven observational studies found that surgical removal of the septum was associated with a low rate of miscarriage (OR 0.25, 95% CI 0.07-0.88), yet there was no difference regarding the live birth rate (OR 1.92, 95% CI 0.37-9.99). 22 The TRUST trial, a multicentre randomized controlled trial published in 2021, also measured the effect of surgical resection of the septum for pregnancy outcomes in women with septate uterus.…”
Section: Uterine Abnormalitiesmentioning
confidence: 99%
“…22 Recentely, a meta-analysis involving seven observational studies found that surgical removal of the septum was associated with a low rate of miscarriage (OR 0.25, 95% CI 0.07-0.88), yet there was no difference regarding the live birth rate (OR 1.92, 95% CI 0.37-9.99). 22 The TRUST trial, a multicentre randomized controlled trial published in 2021, also measured the effect of surgical resection of the septum for pregnancy outcomes in women with septate uterus. Eighty patients were randomized to undergo surgical septum resection (n=40), or expectant management (n=40).…”
Section: Uterine Abnormalitiesmentioning
confidence: 99%